2017
DOI: 10.1089/ten.teb.2015.0559
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Osteogenic Cells from Induced Pluripotent Stem Cells for Bone Tissue Engineering

Abstract: Induced pluripotent stem cells (iPSCs), reprogrammed from adult somatic cells using defined transcription factors, are regarded as a promising cell source for tissue engineering. For the purpose of bone tissue regeneration, efficient in vitro differentiation of iPSCs into downstream cells, such as mesenchymal stem cells (MSCs), osteoblasts, or osteocyte-like cells, before use is necessary to limit undesired tumorogenesis associated with the pluripotency of iPSCs. Until recently numerous techniques on the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 75 publications
0
32
0
1
Order By: Relevance
“…Several studies have also shown that bone formation could be obtained either by the direct use of iPSCs or via prior formation of embryoid bodies. 194 These cell sources seem promising, but it remains to be checked that implanted cells do not form teratomas on the long term.…”
Section: Choosing and Preparing Cells For Btementioning
confidence: 99%
“…Several studies have also shown that bone formation could be obtained either by the direct use of iPSCs or via prior formation of embryoid bodies. 194 These cell sources seem promising, but it remains to be checked that implanted cells do not form teratomas on the long term.…”
Section: Choosing and Preparing Cells For Btementioning
confidence: 99%
“…Along these lines, Wu and colleagues state in their recent review that efficient in vitro differentiation of hiPSCs into downstream cells, such as mesenchymal stem/ stromal cells (MSCs), osteoblasts or osteocyte-like cells is necessary to limit unde- sired tumorigenesis associated with the pluripotency of hiPSCs [49]. They also give good comparisons of the current techniques utilized to confer the induction of hiPSCs into the osteogenic lineage, an evaluation of osteogenic potentials of cells derived from each technique and cells derived from different somatic origins and comparisons of hiPSC-derived MSCs and BMSCs [49].…”
Section: Human Induced Pluripotent Stem Cells (Hipscs)mentioning
confidence: 99%
“…They also give good comparisons of the current techniques utilized to confer the induction of hiPSCs into the osteogenic lineage, an evaluation of osteogenic potentials of cells derived from each technique and cells derived from different somatic origins and comparisons of hiPSC-derived MSCs and BMSCs [49].…”
Section: Human Induced Pluripotent Stem Cells (Hipscs)mentioning
confidence: 99%
“…Induced pluripotent stem cells are cells that are derived from somatic adult cells and have been reprogrammed such that they resemble an embryonic-like state and are capable of indefinite proliferation and can form cells from all three germ line lineages (endoderm, ectoderm and mesoderm) 11 including bone-forming osteoblasts [12][13][14] . We have successfully generated iPSC lines from equines 15 and have developed methods to differentiate the iPSCs into osteoblasts using traditional 2D cell culture techniques 16 .…”
Section: Introductionmentioning
confidence: 99%